1984
DOI: 10.1093/oxfordjournals.aje.a113756
|View full text |Cite
|
Sign up to set email alerts
|

Legionnaires' Disease: The Epidemiology of Two Outbreaks in Burlington, Vermont, 1980

Abstract: Eighty-five cases of Legionnaires' disease were diagnosed in two major outbreaks at a large regional medical center in Burlington, Vermont, in the summer of 1980. Cases in both outbreaks were positive for Legionella pneumophila, serogroup 1 by culture, serology, or direct fluorescent antibody tests. All cases had spent time in the city of Burlington in the 10 days before the onset of symptoms. Cases in both outbreaks were both hospital- and community-acquired. A case-control study identified no common in-hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…Twenty-eight subjects (18 %) reported symptoms compatible with legionellosis in the period [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] April (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-eight subjects (18 %) reported symptoms compatible with legionellosis in the period [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] April (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…They include outbreaks associated with a hot spa [6], fountains [7], a grocery mist machine [8], hot water systems [9], whirlpool baths on a cruise ship [10] as well as evaporative condensers and cooling towers [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…As we learn more about supportive and nonsupportive components of plumbing systems, it may be logical to replace those elements that encourage the growth of legionellae. Once treatment is instituted, microbiologic surveillance of the water must be continued, because resurgence of the bacteria is common and clinical disease may once more result (26,120,157). It has been suggested that dead-end loops in the plumbing system may represent sites in which legionellae can survive and later repopulate the system (44,120).…”
Section: Investigation and Control Of Legionnaires Diseasementioning
confidence: 99%
“…(157). Buffered charcoal-yeast extract agar and selective media (202) had just been introduced into the laboratory through the kind help of James Feeley.…”
Section: Introductionmentioning
confidence: 99%
“…Widely reported sources linked to outbreaks include cooling towers (CTs) [3][4][5][6][7][8][9][10][11] and other aerosol-producing devices [12][13][14][15][16][17][18]. CTs can give rise to large outbreaks accounting for hundreds of LD cases [10,11], because of their capacity to disperse contaminated aerosols over long distances.…”
mentioning
confidence: 99%